Integrating Mawarith in Islamic Social Finance to Advance Economic Growth (SDG 8) and Responsible Consumption (SDG 12) - Puspitasari, Indah; Muhammad, Atha Mahdi; Kayadibi, Saim (Islamic Economics Journal, 2025)
Islamic inheritance law (mawarith) provides a crucial mechanism for ensuring justice and equity in the distribution of wealth among Muslim families. Beyond its personal scope, mawarith holds significant socio-economic potential when linked with Islamic social finance. Drawing on the Islamic moral economy perspective particularly the maqāṣid principle of hifz al-māl, this study examines how utilizing inherited wealth productively, by integrating it with instruments like waqf, zakat, sadaqah, and hibah, can contribute to enhancing inclusive economic growth (SDG 8) and supporting responsible consumption (SDG 12). Using a qualitative method based on analysis of Islamic legal texts and inheritance practices, the study develops a conceptual explanation showing how mawarith ensures fair distribution, reduces the likelihood of disputes, and opens pathways for economic justice and asset sustainability. When integrated with Islamic social finance tools, mawarith has the potential to unlock dormant capital, strengthen community resilience, and encourage locally grounded economic activity. Furthermore, these mechanisms naturally help mawarith advance the achievement of SDG 8 and SDG 12, supporting inclusive growth, circular prosperity, and intergenerational equity. The paper therefore recommends raising awareness of the economic potentials of mawarith and incorporating mawarith into national development policies to realize its full potential. Mawarith linked to Islamic principles on global development goals can be a powerful tool for achieving economic inclusivity and sustainability